Progesterone and autoimmune disease - Hughes, Grant C. (Autoimmunity reviews, 2012)
Sexual dimorphism in human immune systems is most apparent in the female predominance of certain autoimmune diseases (ADs) like systemic lupus erythematosus (SLE). Epidemiologic, observational and experimental evidence strongly suggest sex steroids are important modulators of genetic risk in human AD. In this regard, the roles of progesterone (Pg), an immunomodulatory female sex steroid, are poorly understood. Several lines of investigation indicate Pg and synthetic progestins impact risk of AD and immune-mediated injury in different ways depending on their concentrations and their engagement of various Pg receptors expressed in immune organs, immune cells or tissues targeted by immune attack. At low physiologic levels, Pg may enhance interferon-alpha (IFN-α) pathways important in SLE pathogenesis. Commonly used synthetic progestins may have the opposite effect. At pregnancy levels, Pg may suppress disease activity in rheumatoid arthritis (RA) and multiple sclerosis (MS) via inhibition of T helper type 1 (Th1) and Th17 pathways and induction of anti-inflammatory molecules. Importantly, Pg's immunomodulatory effects differ from those of estrogens and androgens. An additional layer of complexity arises from apparent interdependence of sex hormone signaling pathways. Identifying mechanisms by which Pg and other sex steroids modulate risk of AD and immune-mediated injury will require clarification of their cellular and molecular targets in vivo. These future studies should be informed by recent genetic discoveries in human AD, particularly those revealing their sex-specific genetic associations.